2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--30866
|View full text |Cite
|
Sign up to set email alerts
|

Peer Review and Reflection in Engineering Labs: Writing to Learn and Learning to Write

Abstract: Mexico in the Organization, Information & Learning Sciences program, and in the Chemical & Biological Engineering Department. She served as Co-PI on an NSF RET Grant and a USDA NIFA grant, and is currently co-PI on three NSF-funded projects in engineering and computer science education, including a Revolutionizing Engineering Departments project. She was selected as a National Academy of Education / Spencer Postdoctoral Fellow. Dr. Svihla studies learning in authentic, real world conditions; this includes a tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…We also learned the importance of not making it easy for students to just "accept all" changes, instead focusing on modeling just a few changes and asking students to make the edits themselves. We found that faculty had ideas of various ways to implement these ideas, from using peer-reviews to component submission, yet all of these variants supported student growth, both in terms of conceptual learning and as technical writers, provided the students had to make revisions [52,53].…”
Section: Offer Limited But Specific Feedback On Writing and Require R...mentioning
confidence: 99%
“…We also learned the importance of not making it easy for students to just "accept all" changes, instead focusing on modeling just a few changes and asking students to make the edits themselves. We found that faculty had ideas of various ways to implement these ideas, from using peer-reviews to component submission, yet all of these variants supported student growth, both in terms of conceptual learning and as technical writers, provided the students had to make revisions [52,53].…”
Section: Offer Limited But Specific Feedback On Writing and Require R...mentioning
confidence: 99%